How to Increase Employees’ Innovative Behavior? A Study in A State-Owned Electricity Company - Ahriansyah, Muhammad; Martdianty, Fanny (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This research investigates the impact of high-performance human resource practices (HPHRPs) on employees’ innovative behavior (EIB) both directly and through the mediating effects of work engagement (WE) and psychological capital (PsyCap) in a state-owned electricity company. Design/Methods/Approach: The data was gathered by conducting a survey questionnaire among 722 employees who work in an electricity company. The collected data was then validated through confirmatory factor analysis. The data was analyzed using the covariance-based Structural Equation Modeling (CB-SEM) technique to test the hypotheses. Findings: The findings indicate that HPHRP has a positive impact on Employee Innovative Behaviour (EIB), both directly and indirectly, through the mediation of Work Engagement (WE) and Psychological Capital (PsyCap) in a state-owned electricity company. Originality/Value: This paper is unique as it provides empirical evidence on how high-performance human resource practices impact employees’ innovative behavior directly and with the mediation of work engagement and psychological capital. Practical/Policy implication: HR Managers should focus on employee participation and communication to increase employee work engagement and psychological capital, which will impact innovative behavior among employees. Researchers are encouraged to study employee and organizational performance measures other than Work Engagement and Psychological Capital influenced by high-performance work practices.